2013
DOI: 10.1186/1471-2407-13-13
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cross-sectional study of colorectal cancer screening practices of first-degree relatives of colorectal cancer patients

Abstract: BackgroundThe aim of this study was to determine the proportions and predictors of first-degree relatives (FDRs) of colorectal cancer (CRC) patients (i) ever receiving any CRC testing and (ii) receiving CRC screening in accordance with CRC screening guidelines.MethodsColorectal cancer patients and their FDRs were recruited through the population-based Victorian Cancer Registry, Victoria, Australia. Seven hundred and seven FDRs completed telephone interviews. Of these, 405 FDRs were deemed asymptomatic and elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 52 publications
3
46
2
Order By: Relevance
“…A TOPflash reporter assay was performed in the cells (and APC -mutant SW480 colorectal cancer cells as a positive control) to assess the level of β-catenin/TCF-mediated transcriptional activity. In agreement with previous studies from our laboratory using mammary-derived epithelial and tumor cells (Prosperi et al, 2009; Odenwald et al, 2013), APC knockdown was insufficient to activate reporter activity above baseline (normalized to the activity observed in cells transfected with a mutant FOPflash reporter) (Figure 4A). These findings are also consistent with a lack of cytosolic or nuclear β-catenin accumulation observed in APC-knockdown MDCK cells (data not shown) and failure of APC knockdown in HC11 cells (described earlier) to demonstrate TOPflash reporter activity (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…A TOPflash reporter assay was performed in the cells (and APC -mutant SW480 colorectal cancer cells as a positive control) to assess the level of β-catenin/TCF-mediated transcriptional activity. In agreement with previous studies from our laboratory using mammary-derived epithelial and tumor cells (Prosperi et al, 2009; Odenwald et al, 2013), APC knockdown was insufficient to activate reporter activity above baseline (normalized to the activity observed in cells transfected with a mutant FOPflash reporter) (Figure 4A). These findings are also consistent with a lack of cytosolic or nuclear β-catenin accumulation observed in APC-knockdown MDCK cells (data not shown) and failure of APC knockdown in HC11 cells (described earlier) to demonstrate TOPflash reporter activity (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…Research on the influence of family history of cancer and screening behavior within ethnically diverse populations has been less consistent than would be expected given the connection between family history and personal cancer risk [13,3236]. We found that participants with a family history of cancer were nearly twice as likely to report screening use, but this association was most pronounced in African Americans and US born-Latinos.…”
Section: Discussioncontrasting
confidence: 54%
“…An Australian study reported sibling with high level of education and income also private insurance are more volunteer to participate (25).…”
Section: Discussionmentioning
confidence: 99%